The complete mitochondrial genome of Scapania ampliata Steph., 1897 (Scapaniaceae, Jungermanniales) - Choi, Seung Se (Mitochondrial DNA B Resour, 2021)
Scapania ampliata Steph. is the endemic species in East Asia. To investigate intraspecific variations on mitochondrial genomes of S. ampliata, we completed mitochondrial genome of S. ampliata isolated in Korea. It is 143,664 bp long and contains 73 genes (41 protein-coding genes, three rRNAs, 28 tRNAs, and one pseudogene). 823 single nucleotide polymorphisms (SNPs; 0.057%) and 2,242 insertions and deletions were identified between two S. ampliata mitochondrial genomes, which is large number of intraspecific variations in comparison to the other cases of Bryophyte mitochondrial genomes. Phylogenetic trees show that S. ampliata is clustered with those of two Scapania species with high supportive values.